2020
DOI: 10.1186/s40478-020-01026-0
|View full text |Cite
|
Sign up to set email alerts
|

Trans-synaptic and retrograde axonal spread of Lewy pathology following pre-formed fibril injection in an in vivo A53T alpha-synuclein mouse model of synucleinopathy

Abstract: It is necessary to develop an understanding of the specific mechanisms involved in alpha-synuclein aggregation and propagation to develop disease modifying therapies for age-related synucleinopathies, including Parkinson's disease and Dementia with Lewy Bodies. To adequately address this question, we developed a new transgenic mouse model of synucleinopathy that expresses human A53T SynGFP under control of the mouse prion protein promoter. Our characterization of this mouse line demonstrates that it exhibits s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 91 publications
8
33
0
Order By: Relevance
“…In our paradigm, the tight correlation between DN and (i) degeneration of dopaminergic axon terminals in the striatum ( Figure 5F ), (ii) degeneration of dopaminergic dendrites in the SNr ( Figure 5G ), and (iii) astrogliosis ( Figure 6G ) suggests that the DN pathology is responsible for these observed effects. The functional importance of aSyn pathology in neuronal processes is consistent with the finding of presynaptic aSyn microaggregates in the absence of somatic inclusions ( Spinelli et al, 2014 ), earlier aSyn-induced oxidative stress in the synaptic terminals than in the soma ( Szegő et al, 2019 ; Schaser et al, 2020 ), and the observation that presynaptic aSyn is a primary target for phosphorylation ( Weston et al, 2021 ). As noted above, however, neuritic aSyn pathology often precedes somatic pathology, and cortical neurons with aSyn inclusions degenerate over time ( Osterberg et al, 2015 ).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In our paradigm, the tight correlation between DN and (i) degeneration of dopaminergic axon terminals in the striatum ( Figure 5F ), (ii) degeneration of dopaminergic dendrites in the SNr ( Figure 5G ), and (iii) astrogliosis ( Figure 6G ) suggests that the DN pathology is responsible for these observed effects. The functional importance of aSyn pathology in neuronal processes is consistent with the finding of presynaptic aSyn microaggregates in the absence of somatic inclusions ( Spinelli et al, 2014 ), earlier aSyn-induced oxidative stress in the synaptic terminals than in the soma ( Szegő et al, 2019 ; Schaser et al, 2020 ), and the observation that presynaptic aSyn is a primary target for phosphorylation ( Weston et al, 2021 ). As noted above, however, neuritic aSyn pathology often precedes somatic pathology, and cortical neurons with aSyn inclusions degenerate over time ( Osterberg et al, 2015 ).…”
Section: Discussionsupporting
confidence: 80%
“…Despite the abundance of aSyn pathology ( Figures 4B–D ), nigral dopaminergic neurons and their striatal axon terminals are preserved in the A30P-aSyn transgenic mice used in this study ( Figures 5A–D ; Rathke-Hartlieb et al, 2001 ). In aSyn transgenic mice and in PFF-based models, pathology originates in the presynaptic compartment and propagates retrogradely to the cell body ( Schaser et al, 2020 ). The presence of SA in the A30P-aSyn transgenic mice ( Figure 4C ) therefore suggests that retrograde transport to assemble aSyn aggregates in perinuclear accumulations is preserved in A30P-aSyn mice.…”
Section: Discussionmentioning
confidence: 99%
“…pS129-αsyn positive inclusions were predominantly localized in neurons, suggesting a neuronal selective vulnerability in this model. Previous groups have established that genetic αsyn mouse models with or without PFF treatment can demonstrate the formation of inclusions in glial populations, such as astrocytes, particularly at late stages [38][39][40][41][42]. Few to no inclusions colocalized with the astrocytic marker GFAP at 6 mpi, suggesting that 14-3-3θ's effects on inclusion numbers primarily involve neurons, although we cannot fully rule out the possibility that 14-3-3θ's increase in inclusion numbers at 6 mpi could also reflect some inclusion formation within glial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, we used transgenic mice that express wild-type human sequence alpha-synuclein tagged on its C-terminus with enhanced green fluorescent protein (Syn-GFP) ( 33 ) and intracortical injection of alpha-synuclein preformed fibrils (PFFs) to induce Lewy pathology in Syn-GFP animals as we previously reported ( 34 ). This approach has several advantages, including the ability to study phosphorylation of human sequence protein, the ability to measure alpha-synuclein aggregation in distinct subcellular compartments, and the ability to study the consequences of this aggregation in identified neurons in vivo over a period of months using our established multiphoton imaging paradigm in cortex ( 34 , 35 , 36 , 37 ). Using these approaches, we show that PLK2 contributes to serine-129 phosphorylation of alpha-synuclein at presynaptic terminals, but that its genetic deletion does not change levels of somatic Lewy pathology phosphorylation.…”
mentioning
confidence: 99%